The machine and painting: an investigation into the interrelationship(s) between technology and painting since 1945 - Hennig, Sybille (Rhodes University, Faculty of Humanities, Department of Fine Art, 1986)
Introduction: We, i.e. contemporary Western man, live in a society which has increasingly embraced Science and Technology as the ultimum bonum. The Machine, i.e. Science and Technology, has come to be seen as an impersonal force, a New God - omniscient, omnipotent: to be worshipped and, alas, also to be feared. This mythologem has come to pervade almost every sphere of our lives in a paradigmatic way to the extent where it is hardly ever recognized for what it is and hence fails to arouse the concern it merits. While some of the more perceptive minds - such as Erich Fromm, Rufino Tamayo, Carl Gustav Jung, Konrad Lorenz and Arthur Koestler, to mention but a few - have started ringing the alarm bells, the vast majority of our species seem to plunge ahead with their blinkers firmly in place (more or less contented as long as they can persude themselves that these blinkers were manufactured according to latest technological and scientific specifications). Man's uniquely human powers - his creative intuition, his feelings, his moral and ethical potential, have become sadly neglected and mistrusted. Homo sapiens "“ "homo maniacus" as Koestler suggests? - is now at a crossroads: he has reached a point where the next step could be the last step and result in the annihilation of man as a species. Alternately, avoiding that, there is the outwardly less drastic but essentially equally alarming possibility of men becoming robots, while a third alternative has yet to be found. While it does appear as if a lot of young people, noticeably among students, have started reacting against the over mechanization of life, these reactions often tend to follow the swing-of-the-pendulum principle and veer towards the other extreme, throwing out the baby with the bathwater and falling prey to freak-out cults in a kind of mass-irrationalism, rejecting science and technology altogether. Artists who by their very nature perhaps are particularly sensitive - in a kind of seismographic way - to the currents and undercurrents of their age, have become aware of the effects of science and technology on our way of living, and many of them have in one way or another taken a stand in relation to the position of man in our highly technological world. Looking at the art produced over the last four decades, it is truly astonishing to what extent our changed world reflects in our art - a world and a Weltbild very different from that of our ancestors even just a few generations ago. The purpose of the present study is to survey some of the observations and commentaries that painters and certain kindred spirits from the sciences over the last few decades have offered, in the hope of, if not answering, at least defining and posing anew some of the questions that confront us with ever-increasing urgency.
Keywords: Art and technology; Art, Modern -- 20th century -- History